Catamenial epilepsy: Update on prevalence, pathophysiology and treatment from the findings of the NIH Progesterone Treatment Trial. (May 2015) - Herzog, Andrew G.
Highlights: Seizure occurrence and numbers vary by the day and phase of the menstrual cycle. Seizures vary by the ovulatory versus anovulatory status of menstrual cycles. 3 patterns of catamenial epilepsy: perimenstrual, peri-ovulatory, luteal phase. Reproductive steroids have neuroactive properties that affect neuronal excitability and seizures. Cyclic progesterone supplement may benefit perimenstrually exacerbated seizures. Abstract: Purpose: To extend our knowledge and practical application of the concept of catamenial epilepsy. Methods: The review focuses on the impact of the NIH Progesterone Trial on our understanding of the pathophysiology and treatment of catamenial epilepsy. Results: Catamenial epilepsy refers to the cyclic exacerbation of seizures in relation to the menstrual cycle. An interaction between seizures and the menstrual cycle is suggested by variations in seizure frequency according to the day, phase and ovulatory status of the menstrual cycle. There are three commonly recognized patterns: perimenstrual (C1: Day −3 to +3), peri-ovulatory (C2: Day 10 to 3) and entire luteal phase in anovulatory cycles (C3: Day 10 to 3). Pathophysiological determinants include 1) the neuroactive properties of reproductive steroids, 2) the variation of neuroactive steroid levels across the menstrual cycle and 3) the differential susceptibility of epileptic substrates to neuroactive steroid effects. Perimenstrual seizure exacerbation may result from the premenstrual withdrawal of progesterone which is accompanied by withdrawal of allopregnanolone, a potent positive allosteric modulator of the GABAA receptor, and changes in the subunit composition of the GABAA receptor to the α4 subtype which is insensitive to benzodiazepine and GABA. Bioidentical progesterone supplement is no better than placebo in the treatment of women with focal onset epilepsy overall but shows superior efficacy in women whose seizures show robust perimenstrual exacerbation. Conclusion: There is sound evidence for the existence of catamenial epilepsy and class 3 evidence for adjunctive progesterone treatment of the perimenstrually exacerbated subtype.